2019
DOI: 10.1108/ijoem-12-2017-0521
|View full text |Cite
|
Sign up to set email alerts
|

Co-movement dynamics between global sukuk and bond markets

Abstract: Purpose Market links (and price discovery) between financial assets and lead–lag relationships are topics of interest for financial economists, financial managers and analysts. The lead–lag relationship analysis should consider both short and long-term investors. From a portfolio diversification perspective, the first type of investor is generally more interested in determining the co-movement of financial assets at higher frequencies, which are short-run fluctuations, while the latter concentrates on the rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 78 publications
(88 reference statements)
1
20
0
Order By: Relevance
“…Recent data shows that sukuk issuance has increased in the global market. For example, Malaysia expanded its sukuk issuance to such as Singapore and Turkey (Bhuiyan et al, 2019). On the other hand, The Islamic stock and fund market, which is outside the sukuk market, is still a niche sector (Sidio, 2017, p. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Recent data shows that sukuk issuance has increased in the global market. For example, Malaysia expanded its sukuk issuance to such as Singapore and Turkey (Bhuiyan et al, 2019). On the other hand, The Islamic stock and fund market, which is outside the sukuk market, is still a niche sector (Sidio, 2017, p. 5).…”
Section: Discussionmentioning
confidence: 99%
“…Katrakilidis and Trachanas (2012) revealed that the presence of cointegration indicates drifting apart of variables of the study is only temporary, and will return to equilibrium in the long-run. Bhuiyan et al (2019) examined the lead-lag relationship between Sukuk indices and conventional bond using Johansen Cointegration and wavelet – cross-correlation. The author established no long-run relationship between Malaysia Sukuk and the selected emerging market bond price indices.…”
Section: Theoretical Background and Literature Reviewmentioning
confidence: 99%
“…More specifically, their study investigated several sukuk instruments, reviewed the existing structures, demonstrated sukuk pricing mechanisms and discussed critical issues of each type of sukuk. Bhuiyan et al (2019a) studied the market links (and price discovery) between global sukuk by using the wavelet approach, which has recently been imported to finance from engineering sciences. Hamzah et al (2018) investigated the extent of risk-shifting behaviour in bonds and sukuk.…”
Section: Literature Reviewmentioning
confidence: 99%